Selection of technological parameters in borehole mining production by technical deep drilling and hydroexploitation - Mitrovic Vladimir; Pinka Ján; Dimitrijevic Bojan (Acta Montanistica Slovaca, 2004)
This paper shows the estimate technological parameters for borehole hydro-production of sand by technical deep drilling slim well differently diameters, where are determinate calculation of radius of jet for selects hydro-monitor, the effect of hydro-caving, caving capacity, hydro-transport of pulp and drawings of the most important parts of necessary equipment for exploitation at the mining field exemplified by experimental borerhole hydro-mining of underlying quartz sand at surface open pit mine of coal named the Polje-D in Kolubara.